979 FACTORS THAT INFLUENCE OLDER ADULTS' PARTICIPATION IN PHYSICAL ACTIVITY: A SYSTEMATIC REVIEW OF QUALITATIVE STUDIES. (14th June 2022) - Meredith, S J; Cox, N; Ibrahim, K; Higson, J; McNiff, J; Mitchell,; Rutherford, M; Wijayendran, A; Shenkin,; Kilgour, A; Lim, S E R
Abstract: Introduction: Despite the myriad advantages associated with physical activity (PA), older adults are often insufficiently active to maximise health benefits. Understanding factors that influence engagement in PA will support practitioners in providing well-designed interventions for older people. Our aim was to review the qualitative evidence exploring the factors affecting older adult's engagement in PA. Method: Four electronic databases were searched: CINAHL, Embase, MEDLINE and PsycINFO. Inclusion criteria were community-dwelling older adults (≥70 years), and studies including qualitative method. Exclusion criteria were studies examining a single disease group, individuals with cognitive impairment, care home residents, and PA interventions. The Critical Appraisal Skills Programme (CASP) checklist was used to assess methodological rigour. Framework synthesis using the COM-B model was applied to analyse data, and the GRADE-CERQual approach was used to assess confidence in findings. (PROSPERO: CRD42021160503). Results: Twenty-one studies were included in the review. Participants (N = 3, 955; mean age 78.9 years) included 64% female and 36% male older adults. Most studies were methodologically rigorous (17/21 scored ≥8 CASP). We identified 32 themes mapped against the COM-B framework (16 high confidence). Older adult's perceived capability was influenced by their functional capacity, illness symptoms and perceived risk of injury from PA. PA was motivated by identifying as an 'exerciser', health gains and positive emotions (e.g. enjoyment), while negative sensations reduced motivation (e.g. pain). Opportunity was impacted by the weather, the environment 'fit', and the availability of social interaction during PA. Moreover, social opportunity was impacted by socio-cultural ageing stereotypes and discourses, influencing older adults' PA through media outlets, social norms, and self-stigma. Conclusion: The review found a complex web of interacting factors that influenced older people's PA between the sub-domains of capability, motivation, and opportunity. Future initiatives to increase PA in older adults should focus on social influences, environmental barriers, and physical limitations.